2009
DOI: 10.1353/sof.0.0189
|View full text |Cite
|
Sign up to set email alerts
|

Too Many Friends: Social Integration, Network Cohesion and Adolescent Depressive Symptoms

Abstract: Using a nationally representative sample of adolescents, we examine associations among social integration (network size), network cohesion (alter-density), perceptions of social relationships (e.g., social support) and adolescent depressive symptoms. We find that adolescents with either too large or too small a network have higher levels of depressive symptoms. Among girls, however, the ill effects of over-integration only occur at low levels of network cohesion. For boys, in contrast, the ill effects of over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 61 publications
9
121
1
2
Order By: Relevance
“…Then, Zhou, Shin, Brass and Choi [10] found a curvilinear relationship between the creativity of employees and their weak ties. The individual network analyzed by Falci and McNeely [11] showed a curved linear relation between the size of friend-network and depressive symptoms of teenagers.…”
Section: ) Psychological Variables Effected By Social Network and Somentioning
confidence: 96%
“…Then, Zhou, Shin, Brass and Choi [10] found a curvilinear relationship between the creativity of employees and their weak ties. The individual network analyzed by Falci and McNeely [11] showed a curved linear relation between the size of friend-network and depressive symptoms of teenagers.…”
Section: ) Psychological Variables Effected By Social Network and Somentioning
confidence: 96%
“…The IP does not assess the extent to which participants are socially integrated (central) versus isolated (peripheral) in their social networks' structure. Likewise, the IP limits participants to nominating a maximum of 10 network members, and adolescent networks are undoubtedly larger than that (Falci & McNeely, 2009). The measure was also limited to assessing cigarette use and did not assess use of other tobacco products, such as e-cigarettes.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Researchers also have examined the structural properties of social networks (Falci & McNeely, 2009 ;Haynie, 2001Haynie, , 2002Krohn, Massey, & Zielinski, 1988 ;Schreck, Fisher, & Miller, 2004 ) . These network properties are derived from respondent friendship nominations and describe the connections between an adolescent and the other respondents' nominations, such as how many nominations a respondent receives (popularity), the density of the network, the degree to which members interact with each other in different contexts (multiplexity), or the degree to which a respondent is embedded in the network (centrality).…”
Section: Peersmentioning
confidence: 99%
“…This indicated that whether an adolescent's friends were delinquent mattered more for popular than less popular youth when predicting whether an adolescent was likely to engage in delinquency. Other network research examples include support for the relationship between increased multiplexity and decreased adolescent smoking (Krohn et al, 1988 ) , a decreased risk of violent victimization for youth in dense, conventional networks (Schreck et al, 2004 ) , and higher levels of depressive symptoms in very large or very small networks (Falci & McNeely, 2009 ) . Kreager et al ( 2011 ) recently expanded previous research by examining how group-level characteristics affect network properties.…”
Section: Peersmentioning
confidence: 99%
See 1 more Smart Citation